Determination of the Best Pre-Jump Height for Improvement of Two-Legged Vertical Jump - Jafari, Mahsa (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Athletic performance in many sports depends on two-legged vertical jump. The objective of this study was to examine the effect of different pre-jump height exercises on two-legged vertical jump and to determine the best pre-jump height(s). METHODS: Subjects included 35 females and 42 males. By matched randomized sampling, subjects of each sex were assigned into four groups, namely, control, 10-cm hurdle, 20-cm hurdle, and 30-cm hurdle. They participated in the same training program for 6 weeks. Statistical analyses were based on one-way and repeated-measure analysis of variance (ANOVA). RESULTS: Analysis of the data showed that practice over hurdles of 10 cm was better than no hurdle and hurdles of >10 cm. Also, jump attempts over hurdles were efficient for trained athletes, but not for untrained athletes. For both sexes, the rate of spike improvement was much better in the experimental groups than in the control groups; it was independent from the rate of progress in jump, which was relatively less evident. CONCLUSIONS: It is likely that rather than increasing jump height, training over hurdle enabled the players to use a higher percent of their jump potentials.